Potential of vitamin D food fortification in prevention of cancer deaths: a modeling study - Niedermaier, Tobias; Gredner, Thomas; Kuznia, Sabine; Schöttker, Ben; Mons, Ute; Brenner, Hermann (Nutrients, 2021)
Meta-analyses of randomized controlled trials (RCTs) have estimated a 13% reduction of cancer mortality by vitamin D supplementation among older adults. We evaluated if and to what extent similar effects might be expected from vitamin D fortification of foods. We reviewed the literature on RCTs assessing the impact of vitamin D supplementation on cancer mortality, on increases of vitamin D levels by either supplementation or food fortification, and on costs of supplementation or fortification. Then, we derived expected effects on total cancer mortality and related costs and savings from potential implementation of vitamin D food fortification in Germany and compared the results to those for supplementation. In RCTs with vitamin D supplementation in average doses of 820-2000 IU per day, serum concentrations of 25-hydroxy-vitamin D increased by 15-30 nmol/L, respectively. Studies on food fortification found increases by 10-42 nmol/L, thus largely in the range of increases previously demonstrated by supplementation. Fortification is estimated to be considerably less expensive than supplementation. It might be similarly effective as supplementation in reducing cancer mortality and might even achieve such reduction at substantially larger net savings. Although vitamin D overdoses are unlikely in food fortification programs, implementation should be accompanied by a study monitoring the frequency of potentially occurring adverse effects by overdoses, such as hypercalcemia. Future studies on effectiveness of vitamin D supplementation and fortification are warranted.